Government expenditure and standard of living in an emerging market in Africa–Nigeria - Sarah Elechi Jeff-Anyeneh; Amalachukwu Chijindu Ananwude; Gideon Kasie Ezu; Andrew Izuchukwu Nnoje (Economic Journal of Emerging Markets, 2020)
The effect of government expenditure on the standard of living has different impact for various level of economies. In this study, we determined the effect of government recurrent and capital expenditure on the standard of living in Nigeria using a test of causation. The long and short run estimates were done by utilizing an Autoregressive Distributive Lag (ARDL) model using data that spanned from 1981 to 2018. Findings/Originality: Precipitously, we asserted that government recurrent and capital expenditure have a significant effect on the standard of living in Nigeria. Nevertheless, that is not the true reflection of the living standard in the country. There is an enormous need for the government to increase its expenditure on the health sector. Investment in healthcare is positively related to economic growth and has the potential of reducing poverty, hence a better standard of living. The Federal Government of Nigeria ought to, as a matter of direness, prioritize capital expenditure over recurrent expenditure.